Who pays? CCP resource provision in the post-Pittsburgh world - Jorge Cruz Lopez; Mark Manning (Bank of Canada, 2017)
At the Pittsburgh Summit in 2009, G20 countries announced their commitment to clear all standardized over-the-counter (OTC) derivatives through central counterparties (CCPs). Since then, CCPs have become increasingly important and there has been an extensive program of regulatory enhancements to both them and OTC derivatives markets. However, as OTC clearing has grown, tensions have emerged among market participants over CCPs' traditional model of resource provision through loss mutualization. We argue that most of these tensions can be explained by a misalignment between the policy goal of enhancing financial stability and the delivery of that goal by mandating clearing through CCPs as they are currently organized. Specifically, the traditional model for resource provision makes most CCPs suitable for managing club goods, whereas financial stability is a public good. The key differences between these two types of goods, driven by the wedge between those who pay for them and those who derive the benefits, create the observed tensions. Thus, we propose a framework to analyze the functional elements of a CCP and examine whether an alternative clearing model might be more effective in supporting financial stability. We conclude that some tensions could perhaps be mitigated by unbundling the functions of a CCP and selecting the ownership and funding structure that best suits their individual characteristics. Functions that are critical for the provision of financial stability might imply some form of public sector involvement, whereas other services might lend themselves to a for-profit or traditional club model.
Keywords: G01; G28; 330; Financial markets; Financial stability; Financial system regulation and policies